2019
DOI: 10.1016/j.ajoc.2019.100472
|View full text |Cite
|
Sign up to set email alerts
|

Classification and treatment follow-up of a juxtapapillary retinal hemangioblastoma with optical coherence tomography angiography

Abstract: Purpose Only an endophytic growth pattern in juxtapapillary retinal hemangioblastoma (JRH) is an indication for surgical treatment, but classification of growth types is difficult using conventional imaging techniques. This case report describes the use of optical coherence tomography angiography (OCT-A) features for classification and treatment follow-up in a case with JRH. Observations The JRH of this patient was easily detected with two different OCT-A methods in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…The surgical treatment option is mainly considered for juxtapapillary RCHs with an endophytic growth pattern due to the accessibility of these lesions, 23 whereas intravitreal bevacizumab (with very limited effectiveness) or verteporfin photodynamic therapy can be considered for sessile and exophytic tumors. 24 As shown in a case report by Smid et al, 8 OCTA seems to be a valuable tool for juxtapapillary RCH classification. Smid et al 8 reported OCTA as a possible tool for follow-up after therapy with intravitreal bevacizumab.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The surgical treatment option is mainly considered for juxtapapillary RCHs with an endophytic growth pattern due to the accessibility of these lesions, 23 whereas intravitreal bevacizumab (with very limited effectiveness) or verteporfin photodynamic therapy can be considered for sessile and exophytic tumors. 24 As shown in a case report by Smid et al, 8 OCTA seems to be a valuable tool for juxtapapillary RCH classification. Smid et al 8 reported OCTA as a possible tool for follow-up after therapy with intravitreal bevacizumab.…”
Section: Discussionmentioning
confidence: 91%
“…24 As shown in a case report by Smid et al, 8 OCTA seems to be a valuable tool for juxtapapillary RCH classification. Smid et al 8 reported OCTA as a possible tool for follow-up after therapy with intravitreal bevacizumab. OCTA can also be useful for follow-up after laser photocoagulation, as described in a case series by Lang et al 7 and in a case report by Chou et al 5 Taken together, OCTA can be a helpful diagnostic tool in the diagnosis and follow-up of RCHs.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations